2018
DOI: 10.13189/ujer.2018.061117
|View full text |Cite
|
Sign up to set email alerts
|

Principals’ Perceptions on the Notion of Organizational Culture: The Case of Greece

Abstract: Organizational culture constitutes a fundamental characteristic of the educational organism, because, it contributes to the shape of its character and of its members' way of thinking and behavior and, it is also connected to the employees' productivity and the students' academic performance. It is commonly held that leadership and organizational culture are in a constant process of interaction and heteronomy, constituting two sides of the same coin. Therefore, one of the most important tasks that the education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Introduction Character (i.e., moral, virtue) education is a challenging endeavour in which families and schools should collaborate. School leaders play a pivotal role in achieving a holistic approach to the education process (Tzianakopoulou & Manesis, 2018), embedding an integrated whole-school approach to character education (Walker et al, 2017). But for carrying out this task effectively, they need evidence-based professional development.…”
Section: Mokyklų Vadovų Nuostatos Lūkesčiai Ir įSitikinimai Pradedant...mentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction Character (i.e., moral, virtue) education is a challenging endeavour in which families and schools should collaborate. School leaders play a pivotal role in achieving a holistic approach to the education process (Tzianakopoulou & Manesis, 2018), embedding an integrated whole-school approach to character education (Walker et al, 2017). But for carrying out this task effectively, they need evidence-based professional development.…”
Section: Mokyklų Vadovų Nuostatos Lūkesčiai Ir įSitikinimai Pradedant...mentioning
confidence: 99%
“…Curriculum action research considers participants' expectations, beliefs, values, and their understanding for framing the research: "Context, teacher perceptions and beliefs, learner aspirations and interpretations of the situation, all affect the way in which curriculum intentions are realised in practice" (Pring, 2004, p. 136). Considering theoretical and empirical insights (Chan et al, 2019;Elmeski, 2015;Hourani & Stringer, 2015;Pring, 2004;Romanowski et al, 2019;Tzianakopoulou & Manesis, 2018;Wood & Roac, 2000), it could be concluded that school leaders' expectations, perceptions and self-perceptions, aspirations and interpretations, beliefs and values have to be explored in order to offer a more appropriate professional development programme in terms of its design and delivery.…”
Section: Mokyklų Vadovų Nuostatos Lūkesčiai Ir įSitikinimai Pradedant...mentioning
confidence: 99%
“…An institution’s culture is a set of values and beliefs that form the institution’s identity and are fundamental to improving educational institutions ( Krüger et al, 2007 ). As part of the process of establishing a school’s culture, the school’s long-term goals and direction are set, and traditions, rules of behavior, values, and school visions are used to give the school a sense of cohesion and unity ( Tzianakopoulou and Manesis, 2018 ). School culture is also responsible for ensuring a stable environment within the school community, which contributes to students’ academic excellence ( Turan and Bektas, 2013 ).…”
Section: Introductionmentioning
confidence: 99%